2022
DOI: 10.1155/2022/4147970
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Algorithm‐Based Intraoperative Magnetic Resonance Navigation for Glioma Resection

Abstract: The study aimed to analyze the application value of artificial intelligence algorithm-based intraoperative magnetic resonance imaging (iMRI) in neurosurgical glioma resection. 108 patients with glioma in a hospital were selected and divided into the experimental group (intraoperative magnetic resonance assisted glioma resection) and the control group (conventional surgical experience resection), with 54 patients in each group. After the resection, the tumor resection rate, NIHSS (National Institute of Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In the context of iFC, machine learning algorithms could be trained to recognize subtle patterns, potentially enhancing the accuracy of real-time tumor margin evaluations. This is already a reality for iMRI and the analysis of gliomas [65,66], with promising results. Similar methodologies are already developing for 5 ALA fluorescence analysis [67].…”
Section: Future Prospectsmentioning
confidence: 98%
“…In the context of iFC, machine learning algorithms could be trained to recognize subtle patterns, potentially enhancing the accuracy of real-time tumor margin evaluations. This is already a reality for iMRI and the analysis of gliomas [65,66], with promising results. Similar methodologies are already developing for 5 ALA fluorescence analysis [67].…”
Section: Future Prospectsmentioning
confidence: 98%
“…There was no significant difference in the Karnovsky scores, NIHSS scores, or infection rates between the two groups. The study clearly showed that using AI-MRI interoperative guidance improved tumor resection [ 24 ].…”
Section: Reviewmentioning
confidence: 99%